Transaksi Transfermasi Di BRILink Dalam Perspektif Akad Wakalah Bil Ujrah (Mewakilkan Dengan Imbalan) - Ai Wati; Patimah, Siti (STAI Al Musaddadiyah Garut, 2022)
Transactions conducted through BRILink require an additional nominal amount as an administrative fee, whereas transactions between accounts within BRI Bank are generally not subjected to such fees. However, for inter-bank transactions, administrative fees are applied according to the bank's regulations. This triggers an issue where BRILink imposes additional administrative fees without clear transparency or detailed explanation. The research problem formulation is how transparent are transfer transactions in BRILink, and how are transfer transactions in BRILink viewed from the perspective of wakalah bil ujrah contract. The objective of this research is to understand the transparency of transfer transactions in BRILink and to analyze transfer transactions in BRILink from the perspective of the wakalah bil ujrah contract. The research method used is field research with a qualitative approach. The results of the research indicate that there is currently a lack of transparency regarding administrative fees or ujrah/fee charges, which are not clearly stated in the transaction receipts or evidence. Keywords: Transactions, BRILink transfers, ujrah.